2013
DOI: 10.1371/journal.pone.0072140
|View full text |Cite
|
Sign up to set email alerts
|

Tillage, Mulch and N Fertilizer Affect Emissions of CO2 under the Rain Fed Condition

Abstract: A two year (2010–2012) study was conducted to assess the effects of different agronomic management practices on the emissions of CO2 from a field of non-irrigated wheat planted on China's Loess Plateau. Management practices included four tillage methods i.e. T1: (chisel plow tillage), T2: (zero-tillage), T3: (rotary tillage) and T4: (mold board plow tillage), 2 mulch levels i.e., M0 (no corn residue mulch) and M1 (application of corn residue mulch) and 5 levels of N fertilizer (0, 80, 160, 240, 320 kg N/ha). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
5
10
0
Order By: Relevance
“…On the other hand, Sainju et al [80] demonstrated that N fertilization was able to increase CO 2 flux compared with no N fertilization, probably as a result of accelerated root respiration due to enhanced crop growth. Our results were consistent with those of Tanveer et al [81], who reported that CO 2 emission fluxes increased with the enhancing of crop growth and air temperature. The positive relationship between CO 2 emission and the initial C content may have been attributable to soil microbial activity, which is strongly influenced by C soil content [82].…”
Section: Effect Of Fertilization Methods On Ghgs Emissionssupporting
confidence: 94%
“…On the other hand, Sainju et al [80] demonstrated that N fertilization was able to increase CO 2 flux compared with no N fertilization, probably as a result of accelerated root respiration due to enhanced crop growth. Our results were consistent with those of Tanveer et al [81], who reported that CO 2 emission fluxes increased with the enhancing of crop growth and air temperature. The positive relationship between CO 2 emission and the initial C content may have been attributable to soil microbial activity, which is strongly influenced by C soil content [82].…”
Section: Effect Of Fertilization Methods On Ghgs Emissionssupporting
confidence: 94%
“…We found smaller emissions from MTCC than from CTCC, with both treatments having cover cropping as a common factor. These results are supported by several other studies, indicating that lower tillage frequency and maintenance of crop residues on soil surface promote smaller CO 2 emission (Figueiredo et al., ; Moitinho, Padovan, Panosso, & La Scala, ; Tanveer, Wen, Lu, Zhang, & Liao, ). This suggests that even though the use of cover crop stimulated higher CO 2 emissions in sandy soil, it should be prioritized when using minimum tillage to reduce the amount of CO 2 emitted.…”
Section: Discussionsupporting
confidence: 84%
“…Our results also showed that the association between the cover crop and minimum tillage were efficient methods to promote the mitigation of soil CO 2 emissions in sugarcane fields. These results are in agreement with Figueiredo [ 28 ], Tanveer [ 36 ] and Moitinho [ 37 ], that observed a lower CO 2 emission due to the reduction of the frequency of tillage and maintenance of crop residues on soil surface.…”
Section: Discussionsupporting
confidence: 92%